2013
DOI: 10.1186/1471-2431-13-100
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the pediatric index of mortality 2 (PIM-2) in cardiac and mixed intensive care units in a tertiary children’s referral hospital in Italy

Abstract: BackgroundMortality rate of patients admitted to Intensive Care Units is a widely adopted outcome indicator. Because of large case-mix variability, comparisons of mortality rates must be adjusted for the severity of patient illness at admission. The Pediatric Index of Mortality 2 (PIM-2) has been widely adopted as a tool for adjusting mortality rate by patients’ case mix. The objective of this study was to assess the performance of PIM-2 in children admitted to intensive care units after cardiac surgery, other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 17 publications
6
20
1
1
Order By: Relevance
“…It is likely that in this group of patients, given the low prevalence of CCC (1.2%), the advances in the treatment of critically ill patients have become evident; having improved the prognosis from the time PIM2 was developed. In some populations, these changes have resulted in an observed mortality lower than predicted by PIM2 [31]. This finding has not been evidenced in our sample in the postsurgical patients nor in the miscellaneous diagnoses group, in which the number of observed deaths was higher than the number of deaths predicted by the score, coinciding with what is observed in the general population.…”
Section: Accepted Manuscriptcontrasting
confidence: 77%
See 1 more Smart Citation
“…It is likely that in this group of patients, given the low prevalence of CCC (1.2%), the advances in the treatment of critically ill patients have become evident; having improved the prognosis from the time PIM2 was developed. In some populations, these changes have resulted in an observed mortality lower than predicted by PIM2 [31]. This finding has not been evidenced in our sample in the postsurgical patients nor in the miscellaneous diagnoses group, in which the number of observed deaths was higher than the number of deaths predicted by the score, coinciding with what is observed in the general population.…”
Section: Accepted Manuscriptcontrasting
confidence: 77%
“…Ciofi degli Atti also reported an inadequate calibration of the score in adolescents. These differences could be explained considering that age is not a variable included in the calculation of the score, despite the fact that adolescents are different in many aspects from adults or preadolescents [31,32].…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…15 A prospective study of PIM2 performance in 3 Italian PICUs and one cardiac intensive care unit reported an observed mortality of 4.4% and a predicted mortality of 6.4%, SMR is 0.7 (95% CI 0.6-0.8). 1 In Argentina, a prospective cohort study documented an observed mortality of 2.6% in PICU compared to a PIM2 predicted mortality of 3.06%. 19 A cohort study among children admitted to three PICU settings in Hong Kong revealed a PIM2 predicted mortality (14.2 deaths) compared to 7 observed deaths, SMR is 0.49 (95% CI 0.13 to 0.86).…”
Section: Discussionmentioning
confidence: 99%
“…1 Several scoring models that predict the risk of mortality of pediatric patients admitted to the intensive care are available. 2,3 Mortality prediction models are useful in PICU settings as risk assessment tools and as a benchmark for the quality of care between facilities.…”
Section: Introductionmentioning
confidence: 99%
“…There might be an explanation for such difference because age is not a variable included in the score estimation even though adolescents are different in many aspects compared to adults or pre-adolescents. 21,22 In the analysis of the performance of the PIM2 score stratified by diagnosis group on admission, an adequate discrimination for all categories was observed, except for patients with a diagnosis of a respiratory disease on admission. The calibration also evidenced significant differences between observed and predicted deaths in this group (105 versus 81, p = 0.03).…”
Section: 00mentioning
confidence: 99%